GEODETIC EVIDENCE FOR ACTIVE UPLIFT OF THE OLYMBUS MT, GREECE - Stiros, S.; Triantafillides, P.; Chasapis, A. (Bulletin of the Geological Society of Greece, 2004)
Repeated leveling data collected between 1964-1989 along a traverse crossing the Tempi Valley and the Olymbus Mt (Greece) domai uplift testify to a small, though significant (4-21 ±1.2- 4.7mm) bulging of the central part of the traverse relative to its edges. In combination with coastal observations indicating land uplift at the eastern part of the traverse, as well as with structural and engineering geology observations excluding the possibility the overall pattern of observed displacements to reflect local instability effects, leveling data probably indicate a small amplitude domai uplift. The later is likely to reflect the continuation of the process responsible for the formation of the Olymbus-Ossa Mts, for uncovering of upper mantle rocks and for the impressive incision in the Tempi Valley. Furthermore, the lack of seismicity during the period covered by leveling data indicates that the Olymbus uplift is at least partly associated with aseismic processes.